2020
DOI: 10.3389/fenrg.2020.00160
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Pumped Thermal Energy Storage With De-coupled Thermal Stores

Abstract: Results from the first demonstration of Pumped Thermal Energy Storage (PTES) were published in 2019, indicating an achieved turn-round efficiency of 60-65% for a system capable of storing 600 kWh of electricity. PTES uses a theoretically reversible thermodynamic cycle involving compression and expansion stages with constant pressure heat addition and rejection to hot and cold thermal stores. Energy storage turn-round efficiency largely depends on the isentropic efficiencies of the compression and expansion equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 28 publications
(32 reference statements)
0
3
0
1
Order By: Relevance
“…Dumont and Lemort reported that PTES performs excellently at low air temperatures, high waste heat , and low lift heat pumps [63]. Davenne and Peters simulated a model capable of a roundtrip efficiency of over 50% and having large-scale application areas [64]. A new PTES integrated with thermal heat storage was proposed by Frate, Antonelli, and Desideri and simulated under steady-state conditions [65].…”
Section: Pumped Thermal Energy Storage System (Ptess)mentioning
confidence: 99%
“…Dumont and Lemort reported that PTES performs excellently at low air temperatures, high waste heat , and low lift heat pumps [63]. Davenne and Peters simulated a model capable of a roundtrip efficiency of over 50% and having large-scale application areas [64]. A new PTES integrated with thermal heat storage was proposed by Frate, Antonelli, and Desideri and simulated under steady-state conditions [65].…”
Section: Pumped Thermal Energy Storage System (Ptess)mentioning
confidence: 99%
“…PTES systems that use Packed Bed Heat eXchangers (PBHX) arrangements can be split into two categories: direct-contact, whereby the packed-bed is contained in a pressure vessel and heated by the working fluid of the thermodynamic cycle, and indirect-contact, whereby a secondary heat transfer fluid conveys heat between the working fluid and a bed at ambient pressure. Detailed comparative costing and performance studies between these two approaches conclude that indirect-contact heat exchangers require 30-40% lower plant capital costs [4], though incur a 3.9% lower Round-Trip Efficiency (RTE) versus a comparable direct-contact arrangement [5].…”
Section: Introductionmentioning
confidence: 99%
“…havalandırma sistemi çeşitli sensörlerden oluşmaktadır. Ortamdaki zararlı gazlar belli bir seviyeye çıktığında mevcut havalandırma sistemi devreye girmektedir (Davenne and Peters, 2020). Kontrollü atmosferli depolarda ise normal atmosfer gazlarından farklı olarak değiştirilmiş atmosfer koşullarıyla ortam ayarlanmaktadır.…”
Section: Introductionunclassified